Manganese phytotoxicity: new light on an old problem - Fernando, Denise R.; Lynch, Jonathan P. (Annals of botany, 2015)
Manganese (Mn) is an essential micronutrient that is phytotoxic under certain edaphic and climatic conditions. Multiple edaphic factors regulate Mn redox status and therefore its phytoavailability, and multiple environmental factors including light intensity and temperature interact with Mn phytotoxicity. The complexity of these interactions coupled with substantial genetic variation in Mn tolerance have hampered the recognition of Mn toxicity as an important stress in many natural and agricultural systems. Conflicting theories have been advanced regarding the mechanism of Mn phytotoxicity and tolerance. One line of evidence suggests that Mn toxicity ocurrs in the leaf apoplast, while another suggests that toxicity occurs by disruption of photosynthetic electron flow in chloroplasts. These conflicting results may at least in part be attributed to the light regimes employed, with studies conducted under light intensities approximating natural sunlight showing evidence of photo-oxidative stress as a mechanism of toxicity. Excessive Mn competes with the transport and metabolism of other cationic metals, causing a range of induced nutrient deficiencies. Compartmentation, exclusion and detoxification mechanisms may all be involved in tolerance to excess Mn. The strong effects of light, temperature, precipitation and other climate variables on Mn phytoavailability and phytotoxicity suggest that global climate change is likely to exacerbate Mn toxicity in the future, which has largely escaped scientific attention. Given that Mn is terrestrially ubiquitous, it is imperative that the heightened risk of Mn toxicity to both managed and natural plant ecosystems be factored into evaluation of the potential impacts of global climate change on vegetation. Large inter- and intraspecific genetic variation in tolerance to Mn toxicity suggests that increased Mn toxicity in natural ecosystems may drive changes in community composition, but that in agroecosystems crops may be developed with greater Mn tolerance. These topics deserve greater research attention.